Penerapan Buku Kontrol Pelaksanaan Shalat (BKPS) dalam Meningkatkan Kedisiplinan Shalat Lima Waktu di Era Digitalisasi pada Siswa Kelas VII D SMP Negeri 2 Bontang Tahun Pelajaran 2023-2024 - Hasbulloh, Abdul Wahab; Munir, Misbahul (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
Shalat as the main foundation of a Muslim has an irreplaceable role. This applies in all eras, from the era of the Prophet Muhammad to the current era of digitalization. In order to increase a Muslim's awareness of the importance of the five daily prayers, various learning methods and media have been created, one of which is using a daily journal. The aim of this research is to determine the application of the Prayer Implementation Control Book (BKPS) in an effort to improve the discipline of the five daily prayers of class VII D students at SMPN 2 Bontang and to determine the increase in discipline of the five daily prayers by implementing this book in the era of digitalization. This research is a type of qualitative research, namely research whose findings are not obtained through statistical procedures but rather based on the researcher's approach to the process of understanding and interpreting field conditions. Data was obtained from observations, interviews and documents. The research results show that the Prayer Implementation Control Book (BKPS) is a daily journal consisting of 14 pages. The use of this book is for students, students are asked to fill in the tables contained in it every day according to actual conditions. The use of the Prayer Implementation Control Book (BKPS) is effective in improving the prayer discipline of class VII D students at SMP Negeri 2 Bontang. The data source states that with the existence of BKPS they are aware that as Muslims they have the obligation to pray five times every day. So as to bring out the expected disciplined character.